Chelerythrine Inhibits the Secretory Response of Human Blood Platelets Without Specifically Inhibitng Protein Kinase C [Sample] - Lane, Trevor; Nova, Philipp (1997)
Chelerythrine (chloride) has previously been documented to be a potent and selective inhibitor of the serine/theonine-specific protein kinase C (PKC). In this study, it was shown that 10 uM chelerythrine completely inhitbited serotonin secretion and partially inhibited phosphatidic acid formation, in human blood platelets activated by thombin, (1 U/ml.) However , there was no effect on PKC activity, as assessed by the level of phosphorylation of the 47 Kd protein. Therefore, cherythrione has been shown not to be a specific inhibitor of PKC and without specifically affecting PKC activity, is nevertheless capable completely inhibiting platelet secretion, indicating that it may affect the signal transduction pathway responsible for platelet secretion at a point downstream or independent of PKC.
Keywords: Acid deposition